The effects of sensory integration technique on equilibrium processes in children after prenatal exposure to alcohol - Wilczyński, Jacek; Sowińska, Anita; Wilczyński, Igor (Journal of Education, Health and Sport, 2017)
ABSTRACT Background:The objective of the study was evaluation of sensory integration therapy effectiveness in children after prenatal exposure to alcohol, on the example of equilibrium processes. Material and methods: The study was conducted in 2012 at the Centre of Advanced Physiotherapy in Kielce, and covered a group of 20 children aged 4-5 who had a history of prenatal exposure to alcohol. The children systematically participated in a one-hour SI therapy session, once a week for the period of 6 months. Results: While evaluating the equilibrium system, 5 trials with clinical observations were performed according to Ayres: the Schilder test, dynamic and static balance, gravitational uncertainty, and postrotary nystagmus. The high effectiveness of SI therapy was confirmed in children subjected to prenatal alcohol exposure based on the example of the equilibrium system. The positive effects of therapy were proved for all the tests applied: the Schilder test (p<0.001), dynamic balance (p<0.001), static balance (p<0.001), gravitational insecurity (p<0.001), and postrotary nystagmus (p<0.05). Conclusions: The sensory integration technique exerts a beneficial effect on the balance functions of children after prenatal exposure to alcohol.